Etnopadegogi: Pembelajaran Bahasa dan Sastra Indonesia di Kalangan Siswa Sekolah Dasar: Ethnopadegogy: Learning Indonesian Language and Literature Among Primary School Students - Dirgantari, Nadila; Cahyani, Isah (Kibas Cenderawasih, 2024)
The purpose of this research is that learning Indonesian Language and Literature, which is applied at the SD/MI level, can develop. Opportunities for students to demonstrate scientific behaviour, namely curiosity; earnestness; thorough; alert as a form to apply attitudes in conducting research and scientific discussions to achieve awareness and concern for society or the environment, knowing and understanding basic concepts to solve social problems according to their psychological development, developing critical thinking. The method used is the method of literature by studying related references in the form of theory. The results of the ethnopedagogical study became an alternative learning method used to develop the learning process of the Indonesian language and literature as a learning resource.